How are microbial and detrital sources partitioned among and within gastropods species at East Pacific Rise hydrothermal vents?. (August 2015) - Gaudron, Sylvie M.; Marqué, Lise; Thiébaut, Eric; Riera, Pascal; Duperron, Sébastien; Zbinden, Magali
Abstract: For the last few decades, trophic ecology has usually been investigated by using stable isotopes. However, the isotopic signatures of potential food sources in hydrothermal vent ecosystems are often unknown and so their relative contribution to the consumers' diet, as well as resource partitioning, are then difficult to estimate. Here, we used a recent Bayesian mixing model (stable isotope analysis in R, SIAR) based on δ 13 C and δ 15 N to estimate the contribution of multiple food sources to the diet of eight vent gastropods that can reach high densities at hydrothermal vents ( Lepetodrilus elevatus, Lepetodrilus pustulosus, Lepetodrilus ovalis, Eulepetopsis vitrea, Cyathermia naticoides, Peltospira delicata, Peltospira operculata and Rhynchopelta concentrica ). These species, known as primary consumers (mostly bacterivores and detritivores), were sampled on the South‐East Pacific Rise at 17°25′ S and the North‐East Pacific Rise at 9°50′ N and 12°50′ N. Several potential food sources were sampled according to the gastropod habitat on the chimney wall, or mussel beds (proxies of Gammaproteobacteria form I RubisCO, Gammaproteobacteria form II RubisCO and Epsilonproteobacteria, biofilms of siboglinid and alvinellid tubes, biofilms of mussel shells and particulate organic matter). Some of these microbial and detrital sources were confirmed as present in the gut content of some small specimens by transmission electron microscopy. Distinct stable isotopic signatures of the potential food sources allowed calculation of their relative contributions to primary consumers' diets. This revealed that gastropod species living on siboglinid or bathymodiolin habitats are usually generalists, feeding on various pools of microbial or detrital origins. For a particular habitat, sympatric gastropod species partition the food sources, thus avoiding being in competition. Only for the alvinellid habitat Peltospira spp. appeared to be more specialists as the choice of food sources is more reduced.